2013
DOI: 10.1186/1472-6831-13-19
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries among children visiting a mobile dental clinic in South Central Kentucky: a pooled cross-sectional study

Abstract: BackgroundDental caries is one of the most common chronic childhood diseases affecting a large portion of children in the United States. The prevalence of childhood dental caries in Kentucky is among the highest in the nation. The purposes of this study are to (1) compare sociodemographic differences between caries and no caries groups and (2) investigate factors associated with untreated dental caries among children who visited a mobile dental clinic in South Central Kentucky.MethodsStudy subjects were childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 36 publications
(36 reference statements)
6
33
0
Order By: Relevance
“…Community school‐based programmes provide millions of low‐income and uninsured children with oral health care who would not receive treatment otherwise Research in the United States from 1960 to 2014 has established dental sealants as a highly effective means for caries prevention in low socioeconomic status (SES) children who are identified as a high caries risk population . Conversely, the extent of the benefit of dental sealants for children with moderate to low caries risk is not well established due to a lack of quality research . Therefore, school‐based sealant programmes should target schools with low SES children for caries prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Community school‐based programmes provide millions of low‐income and uninsured children with oral health care who would not receive treatment otherwise Research in the United States from 1960 to 2014 has established dental sealants as a highly effective means for caries prevention in low socioeconomic status (SES) children who are identified as a high caries risk population . Conversely, the extent of the benefit of dental sealants for children with moderate to low caries risk is not well established due to a lack of quality research . Therefore, school‐based sealant programmes should target schools with low SES children for caries prevention.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study insurance coverage, age and residential location are statistically significant in dental caries status while gender or race and ethnicity are non-significant in dental caries status [16]. In this study was found about 50% children (0-5 y.)…”
Section: Discussionmentioning
confidence: 59%
“…Poor oral health is associated with other diseases (low-birth weight and cardiovascular disease) [16]. In a previous study insurance coverage, age and residential location are statistically significant in dental caries status while gender or race and ethnicity are non-significant in dental caries status [16].…”
Section: Discussionmentioning
confidence: 99%
“…Several risk factors associated with children's untreated decay have been identified in the literature including older age, rural residence, and poverty. The results of studies that have investigated the association of age and geographic location with having untreated tooth decay are inconclusive [4] [14]- [17]. Weyant et al explored the prevalence of oral health status among school children in grades 1, 3, 9, and 11.…”
mentioning
confidence: 99%